2017
DOI: 10.14746/ssllt.2017.7.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Language aptitude: Desirable trait or acquirable attribute?

Abstract: The traditional definition of language aptitude sees it as "an individual's initial state of readiness and capacity for learning a foreign language, and probable facility in doing so given the presence of motivation and opportunity" (Carroll, 1981, p. 86). This conception portrays language aptitude as a trait, in the sense of exhibiting stability over long periods of time and being immune to training. The trait view of language aptitude tends towards the notion that it is innate, and indeed language aptitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 48 publications
(47 reference statements)
1
24
0
2
Order By: Relevance
“…The results from the present study serve to empirically confirm Meara's () original caution concerning potential validity issues with the LLAMA (see also Singleton, , ). As a whole, the LLAMA battery exhibits weaknesses at all three levels of inference that we tested (a potential exception being LLAMA B) and is therefore clearly not suitable for use in situations where performance has important consequences for test takers (e.g., opportunities for education and employment).…”
Section: Discussionsupporting
confidence: 82%
“…The results from the present study serve to empirically confirm Meara's () original caution concerning potential validity issues with the LLAMA (see also Singleton, , ). As a whole, the LLAMA battery exhibits weaknesses at all three levels of inference that we tested (a potential exception being LLAMA B) and is therefore clearly not suitable for use in situations where performance has important consequences for test takers (e.g., opportunities for education and employment).…”
Section: Discussionsupporting
confidence: 82%
“…Individuals with a high aptitude for something mostly put little effort into acquiring a certain skill and need far less time and practice to reach a high achievement or proficiency level in comparison to age-matched peers ( Carroll, 1958 , 1962 , 1990 ). The concept of language aptitude has gained considerable momentum in the past decades and research has shown that various factors contribute to the overall achievement and proficiency of skills, e.g., environmental influences, personality traits, motivation and other abilities such as musicality or working memory ( Ganschow and Sparks, 1995 ; Dörnyei, 1998 , 2006 ; Sparks and Ganschow, 2001 ; Brown, 2006 ; Biedroń and Szczepaniak, 2009 ; Rota and Reiterer, 2009 ; Biedroń, 2011a , b , 2012 ; Sparks et al, 2011 ; Wen, 2012 , 2016 ; Christiner and Reiterer, 2013 ; Granena and Long, 2013 ; Dörnyei and Ryan, 2015 ; Li, 2015 , 2016 ; Biedroń and Pawlak, 2016a , b ; Singleton, 2017 ; Wen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive factor investigated in the present study, working memory, has been found to be a robust predictor of second language learning (for recent reviews, see Wen, 2016;Wen et al, 2017;Singleton, 2017), above all in studies on vocabulary and grammar learning (Sanz, Lin, Lado, Stafford & Bowden, 2014). However, few studies (Gilabert & Muñoz, 2010;Guara-Tavarés, 2013;Kormos & Safar, 2008;Kormos, 2012b;Kormos & Trebits, 2011;Mota, 2003;Tagarelli, Ruiz, Moreno & Rebuschat, 2016;Zalbidea, 2017) have examined the relationship between working memory and different dimensions of language performance, namely, complexity (both structural and lexical), accuracy and fluency (henceforth, CAF).…”
Section: Background Of the Studymentioning
confidence: 82%
“…Research on the role of individual differences (IDs) in second language learning and performance has increased in recent years thanks to a renewed interest in inter-individual variation caused by differences in cognitive abilities such as working memory, and also to the re-examination of working memory as a component of language aptitude explaining success in language learning (Doughty, 2018;Singleton, 2017). The present study is a contribution in this line of investigation, as it addresses the potential effect that different components of working memory may have on the accuracy, fluency and complexity of L2 written production.…”
Section: Introductionmentioning
confidence: 99%